Optimizing Xenograft Models for Breast Cancer: A Comparative Analysis of Cell-Derived and Patient-Derived Implantation Techniques in Pre-Clinical Research - Khairani AF; Harmonia S; Chou Y; Alfarafisa NM; Ramadhanti J (Breast Cancer: Targets and Therapy)
Astrid Feinisa Khairani,1– 3 Shella Harmonia,2 Yoan Chou,3 Nayla Majeda Alfarafisa,1,2 Julia Ramadhanti1,2 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 2Undergraduate Program, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 3Graduate School of Master Program in Anti Aging and Aesthetic Medicine, Faculty of Medicine, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Astrid Feinisa Khairani, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jalan Ir. Soekarno KM.21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Email astrid.khairani@unpad.ac.idPurpose: The high mortality rate of breast cancer motivates researchers to search for effective treatments. Due to their ability to simulate human conditions, xenograft models such as CDX (Cell line-Derived Xenografts) and PDX (Patient-Derived Xenografts) have gained popularity in pre-clinical research. The choice of xenograft technique is influenced by the type of tumor employed, particularly in more aggressive tumor models like TNBC with metastases. Subcutaneous or orthotopic implantation may influence tumor engraftment rates and the applicability of the models for drug testing. To optimize xenograft models and support the development of breast cancer drugs, selecting a suitable transplantation technique is essential to attaining the best results.Methods: This scoping review used PRISMA-Scr methodology to summarize findings from eleven articles published between 2012 and 2024 on pre-clinical trials related to xenograft models for breast cancer considering PDX began traction after 2010. Using specific criteria, the review included studies from electronic platforms. The inclusion criteria ensured relevant English sources were available in full text, while the exclusion criteria eliminated certain types of articles and inadequately comprehensive studies.Results: Subcutaneous and orthotopic implantation are critical methods for xenograft models in cancer research. Subcutaneous implantation is less invasive and more manageable but does not fully mimic the tumor’s natural environment. Orthotopic implantation accurately mimic the migration, invasion, and molecular characteristics of the original tumor, although the procedure is more complex and requires specialized techniques. The specific research objectives determine their choice, the need for accurate tumor replication, and the testing convenience.Conclusion: Orthotopic implantation is the preferable method for developing PDX and CDX models of breast cancer because it closely mimics the tumor microenvironment and metastatic behavior, yielding clinically relevant results for drug testing. Subcutaneous implantation may result in higher engraftment rates, but it cannot accurately represent the complexity of tumors.Keywords: breast cancer, implantation, orthotopic, subcutaneous, xenograft